Analysis of reputation effect, attractiveness of advertising and community effects on positive word of mouth with variable intervening customer values on users of gsm-based cellular cards in Palembang City / Megawati and Sri Megawati Elizabeth - -, Megawati; -, Sri Megawati Elizabeth (UiTM Cawangan Johor, 2019)
The purpose of this study was to analyze the impact of reputation, advertising attractiveness, and also community effect on Positive Word of Mouth (WOM). Customers value was employed as an intervening variable. Both primary data and secondary data were employed. The secondary data were gathered using questionnaire which was distributed to the target respondents. The respondents were the users of cellular-phone card in Palembang. Using a convenience sampling technique, a total sample of 180 respondents was obtained. Data were analyzed using Structural Equation Modeling. The results showed that only community effect had a significant impact on customer value and WOM. The result indicated that this variable i.e. community effect is an important part for the customers and is a rapid way for the promoting the value of the product. Further, the result showed that customer value had a significant effect on WOM.